Health information seeking behavior and socioeconomic influences among parents of children with Autism Spectrum Disorder (ASD): implications for support and interventions / Nora Lina Mohd Hussain, Shamila Mohamed Shuhidan and Ap-azli Bunawan - Mohd Hussain, Nora Lina; Mohamed Shuhidan, Shamila; Bunawan, Ap-azli (Faculty of Information Management, 2023)
Autism Spectrum Disorder (ASD) is a worldwide public health concern that poses unique challenges for both people on the spectrum and their families. It is critical that the world recognizes the magnitude of the problem without discrimination based on socioeconomic reasons. The goal of this study is to look at the relationship between health information-seeking behavior (HISB) and socioeconomic factors in parents of autistic children, as well as the implications for support and therapies. This paper presents the conceptual framework of health information seeking behavior and socioeconomic influences among parents of children with autism spectrum disorder (ASD) on the impact of socioeconomic factors such as parent’s age, income, qualification, and occupation as factors that may lead on their information-seeking tendencies. This study will be using a quantitative method. The findings have important consequences for both research and practice. It may help the government, nongovernmental organizations, and autism research centers provide specific support services and interventions in the development of policies and programs that address knowledge and resource gaps, thereby increasing the well-being of ASD households.